Pengaruh Pemberian Tablet Ekstra Ikan Gabus dengan Proses Penyembuhan Jahitan Luka Post SC - Nita Safitri; Qomariyah Qomariyah; Kristina Maharani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
A Caesarean section, or C-section, is a surgical procedure where a baby is delivered through an incision made in the mother’s abdomen and uterus. To aid the healing of post-Caesarean wounds, mothers need not only antibiotics but also a diet that provides high-quality nutrition and adequate calories. The research question being investigated is: